1980
DOI: 10.1073/pnas.77.10.5688
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the slow reacting substances from cat paws.

Abstract: Perfusion of cat paws with compound 48/80 released two slow reacting substances (SRSs) which were isolated and characterized as 5-hydroxy-S-cysteinylglycyl-7,9,-11,14-icosatetraenoic acid (SRS I) and -hydroxy-6S-cysteinyl-7,9,11,14-icosatetraenoic acid (SRS II) on the basis of chemical degradations, amino acid analyses, spectroscopic and enzymic experiments, and comparison with synthetic samples. The smooth muscle-contractile activities of synthetic 5-hydroxy-6 y-glutamylcysteinylglycyl-7,9,11,14-icosatetraeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Peak la was characterized as SRS-GSH on the basis of the following observations: Its ultraviolet absorption spectrum showed a maximum at 280 nm with shoulders at 270 and 292 nm; its retention time was identical to that of synthetic SRS- (11); and amino acid analysis (Table 1) indicated that the molecule contained glutamic acid, cysteine, and glycine. Calculated on the basis of the ultraviolet absorbance at 280 nm, approximately 1 mol of glutamic acid and 1 mol of glycine per mol of SRS were obtained.…”
Section: -Icosatetraenoic Acid (Srs-gsh)mentioning
confidence: 99%
See 1 more Smart Citation
“…Peak la was characterized as SRS-GSH on the basis of the following observations: Its ultraviolet absorption spectrum showed a maximum at 280 nm with shoulders at 270 and 292 nm; its retention time was identical to that of synthetic SRS- (11); and amino acid analysis (Table 1) indicated that the molecule contained glutamic acid, cysteine, and glycine. Calculated on the basis of the ultraviolet absorbance at 280 nm, approximately 1 mol of glutamic acid and 1 mol of glycine per mol of SRS were obtained.…”
Section: -Icosatetraenoic Acid (Srs-gsh)mentioning
confidence: 99%
“…The system contained: 0.8 unit of y-glutamyl transpeptidase (bovine); 55 nmol of synthetic SRS-GSH (11), and 10 mM MgCl2 in 1 ml of 0.05 M Tris-HCl buffer, pH 8.5. Incubation was carried out with and without 10 mM L-cysteine. After 30 min, 4 ml of cold ethanol was added to the reaction mixture, which was allowed to stand for 30 min at SoC.…”
Section: -Icosatetraenoic Acid (Srs-gsh)mentioning
confidence: 99%
“…Therefore, it has been suspected that the inactivation of SRS-A by the arylsulfatase preparation is due to a contaminating protease rather than to the arylsulfatase itself. This enzyme preparation cleaves the peptide bond in highly bioactive LTD4 (SRS-cystinyl glycyl form) to form much less bioactive LTE4 (SRS-cystinyl form) (8,20,21). In our experiments, limpet arylsulfatase type V which was contaminated by aminopeptidase activity markedly inactivated LTD4 and inactivated guinea pig SRS-A and rat SRS to a lesser extent, but did not inactivate LTC4 and human SRS at all (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…This transformation increases the biological activity on the guinea pig ileum (8,9). In this study, the activity of LTD4 was about 10 times more potent than that of LTC4 in the isolated guinea pig ileum (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation